Voices from the frontline: barriers and strategies to improve tuberculosis infection control in primary health care facilities in South Africa - Farirai Zinatsa; Michelle Engelbrecht; André Janse van Rensburg; Gladys Kigozi (BMC, 2018)
Abstract Background Tuberculosis (TB) infection control at primary healthcare (PHC) level remains problematic, especially in South Africa. Improvements are significantly dependent on healthcare workers' (HCWs) behaviours, underwriting an urgent need for behaviour change. This study sought to 1) identify factors influencing TB infection control behaviour at PHC level within a high TB burden district and 2) in a participatory manner elicit recommendations from HCWs for improved TB infection control. Method A qualitative case study was employed. TB nurses and facility managers in the Mangaung Metropolitan District, South Africa, participated in five focus group and nominal group discussions. Data was thematically analysed. Results Utilising the Information Motivation and Behaviour (IMB) Model, major barriers to TB infection control information included poor training and conflicting policy guidelines. Low levels of motivation were observed among participants, linked to feelings of powerlessness, negative attitudes of HCWs, poor district health support, and general health system challenges. With a few exceptions, most behaviours necessary to achieve TB risk-reduction, were generally regarded as easy to accomplish. Conclusions Strategies for improved TB infection control included: training for comprehensive TB infection control for all HCWs; clarity on TB infection control policy guidelines; improved patient education and awareness of TB infection control measures; emphasis on the active role HCWs can play in infection control as change agents; improved social support; practical, hands-on training or role playing to improve behavioural skills; and the destigmatisation of TB/HIV among HCWs and patients.